Environmental management as a component of Ukraine’s modern economy: Management under the conditions of martial law - Fedorenko, Stanislav; Vasylenko, Lesya; Bereznytska, Yuliia; Kravchenko, Maryna (Construction of Optimized Energy Potential (CoOEP), 2022)
The development of environmental management in Ukraine is determined by the urgent need to overcome environmental problems and ensure the environmental safety of society, especially under the conditions of martial law. Today, the domestic economy is three times more resource-intensive than the world economy, the technological base and infrastructure complex of public production are rapidly wearing out, which leads to a decrease in the level of technological and environmental safety. Environmental management is related to the national economy and forms information about the need to use natural resources when promoting effective development. A comprehensive project-targeted approach to the develop ment of new forms of ownership and market economy reflects the interrelationship of all parts of the nature management project. The development of the scientific foundations of nature management is facilitated by the formulation of a general plan for the placement of productive forces. The ecological situation in Ukraine has long been called a crisis. In recent decades, new scientific directions have appeared, the result of which have been new ideas about human, society and nature and their coexistence. One of these directions is environmental management, which today is the ideology of production activity manage ment, as it provides an effective toolkit for solving current problems and preventing the emergence of new production environmental and economic issues.
Keywords: Department of Environmental Protection and Labor Protection Technologies; eco-management; eco-safety; natural resources; ecosystem; martial law